Mentoring and Empowerment Diploma Three Student in Blood Bank Technology, Health Polytechnic, Ministry of Health, Semarang, Through Training in Making Soy Milk as an Effort to Prevent Anemia - Afrianti, Dina; Hartono, Rodhi; Setyowatiningsih, Lilik; Sofyanita, Eko Naning; Wahyudi (CV Media Inti Teknologi, 2024)
Mentoring participants know about anemia and its symptoms. Participants know the equipment and materials needed to make soy milk and know the steps on how to make soy milk and participants are able to give a demonstration of making soy milk to the residents of the target village. Residents of the assisted villages know how to make soy milk. Community service activities with the Entrepreneurship Development Program (PPK) scheme with the theme